2010
DOI: 10.1002/ajmg.c.30273
|View full text |Cite
|
Sign up to set email alerts
|

Prader–Willi syndrome and Angelman syndrome

Abstract: Prader-Willi syndrome (PWS) and Angelman syndrome (AS) are two distinct neurogenetic disorders in which imprinted genes on the proximal long arm of chromosome 15 are affected. Although the SNORD116 gene cluster has become a prime candidate for PWS, it cannot be excluded that other paternally expressed genes in the chromosomal region 15q11q13 contribute to the full phenotype. AS is caused by a deficiency of the UBE3A gene, which in the brain is expressed from the maternal allele only. The most frequent genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
242
0
12

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(255 citation statements)
references
References 111 publications
1
242
0
12
Order By: Relevance
“…64,65 AS is usually associated with genetic abnormalities at an imprinted cluster containing UBE3A within 15q11-q13, and approximately 2-4% of the patients show epigenetic defects at this region, which include loss of methylation at the ICR at an imprinted bicistronic transcript encoding small nuclear ribonucleoprotein N (SNRPN) and SNRPN upstream reading frame (SNURF) (referred to as SNRPN) (Figure 2 and Table 1). [66][67][68] Among those, 92% are thought to have epigenetic mutations occurring in either oocytes or early embryos. 66 Maternally transmitted deletions of a region located 35 kb upstream of the SNRPN ICR, along with loss of methylation, have been identified in AS patients, which led to the discovery of the AS-imprinting center.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
See 3 more Smart Citations
“…64,65 AS is usually associated with genetic abnormalities at an imprinted cluster containing UBE3A within 15q11-q13, and approximately 2-4% of the patients show epigenetic defects at this region, which include loss of methylation at the ICR at an imprinted bicistronic transcript encoding small nuclear ribonucleoprotein N (SNRPN) and SNRPN upstream reading frame (SNURF) (referred to as SNRPN) (Figure 2 and Table 1). [66][67][68] Among those, 92% are thought to have epigenetic mutations occurring in either oocytes or early embryos. 66 Maternally transmitted deletions of a region located 35 kb upstream of the SNRPN ICR, along with loss of methylation, have been identified in AS patients, which led to the discovery of the AS-imprinting center.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
“…[66][67][68] Among those, 92% are thought to have epigenetic mutations occurring in either oocytes or early embryos. 66 Maternally transmitted deletions of a region located 35 kb upstream of the SNRPN ICR, along with loss of methylation, have been identified in AS patients, which led to the discovery of the AS-imprinting center. 69,70 The SNRPN gene has a number of alternative transcripts, and AS-imprinting center overlaps with exons of such transcripts.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
See 2 more Smart Citations
“…Children affected by severe ID and/or ASD are generally born to healthy parents, and accordingly de novo chromosomal translocations and aneuploidy are major causes of these disorders (van Bokhoven 2011). Other modes of inheritance consistent with sporadic disorder are autosomal recessive, X-linked, and imprinting, and examples of all of these are also found for severe ID (des Portes 2013; Musante and Ropers 2014;Buiting 2010). Recently, sequencing of probands and parents has confirmed that single de novo protein-altering mutations are also causal in a significant proportion of cases (Gilissen et al 2014;Krumm et al 2014;Veltman and Brunner 2012).…”
Section: Intellectual Disability and Autism Spectrum Disordersmentioning
confidence: 99%